A Simple Technique Based on Digital Images for Determination of Nitrogen Dioxide in Ambient Air - de França Souza, Pedro Augusto [UNESP]; Araújo Neto, José Lozano [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Springer Nature, 2021)
The lockdown to prevent the coronavirus spread resulted in an immediate reduction in gas concentration worldwide. This fact shows the importance of nitrogen dioxide as a pollutant gas directly associated with human activities. For indoor exposure, NO2 has been associated with effects on the respiratory system. In outdoor environments, ozone reaches a maximum after NO2 peaks, and acid rain arises with NO2 oxidation to forms nitric acid. Therefore, monitoring the NO2 concentration in atmospheric air can help prevent respiratory diseases and lower the concentration of other atmospheric pollutants. The experiment proposed in this article uses a low-cost passive sampler for the NO2 collection. An innovative and straightforward technique to determine the gas concentration through a gel-dyed formation and based on digital image analysis RGB colors channel are split by the software ImageJ. Results of digital image analysis and spectrophotometry were statistically agreed at a 95% confidence level. The advantages of the technique include low cost, the ready availability of components, ease of use, and sensitivity. The achievable resolution of nitrogen dioxide concentrations is 9 ppb for 24-h sampling.
Keywords: Air pollution; Air quality; Colorimetry; Digital image analysis; NO2 monitoring; Passive sampling